International migrations: some comparisons and lessons for the European Union - Giovanni Peri (University of California, Department of Economics, 2005)
The revival of international migration in the last fifteen years has spurred economists to more systematically study their determinants and consequences. This contribution expands the existing literature in two directions. First we focus on the European Union as a whole and compare it to the US and other countries with net immigration (Canada, Australia and Switzerland). In so doing we establish some important facts about their capacity to attract migrant, and to foster internal migration across countries. Second, we analyze more systematically the causes and consequences of international migration of workers with different educational levels. We use a recent data set based on census information on natives and foreign born in 28 OECD countries for the year 2000. Four important facts emerge: 1) The European Union, far from acting like an integrated labor market (such as the US), exhibits low levels of cross-country internal mobility (for all skill levels) even compared to other OECD countries. 2) The European Union lags far behind the US and other immigration countries (Canada, Australia, Switzerland) in its ability to attract immigrants from outside (for all skills levels). 3) While typical immigration economies attract international migrants whose schooling achievements are complementary to those of natives, thus increasing wages for a majority of their natives, the EU attracts immigrants whose education levels mirror those of its natives and may depress wage for a majority of them. 4) Within the EU, Great Britain is the most similar to the immigration economies in terms of its ability to attract skilled migrants and in the composition of immigrants across schooling groups.
Keywords: F22; J31; 330; Determinants of International Migrations; Impact of Migrations; Skills; Migration Policies; European Union